Pengaruh Kualitas Produk, Cashless Transaction, dan Emotional Design terhadap Kepuasan Konsumen - safitri safitri; Anjar Dwi Astono (UNIVERSITAS KALBIS, 2026)
The purpose of this research to understand the effect of product quality, cashless transactions and emotional design on customer satisfaction at pecel lele stalls in Johar Baru, Jakarta. This type of research utilizes a quantitative method. The sample harvesting technique uses a purposive sampling of 140 respondents who have purchased products directly at the Johar Baru pecel lele shop, Jakarta. The analysis technique used in this research is validity test, reliability rest, classical assumption test, multiple linear regression test, and hypothesis testing. The results of the hypothesis test show that the variable product quality has no significant effect on customer satisfaction, while cashless transactions and emotional design have a significant effect on customer satisfaction. Moreover, Product quality, cashless transaction and emotional design simultaneously have a significant influence on consumer satisfaction.